Epistemology of education policies: some conceptual accuracies - Dermeval Saviani (Red Latinoamericana de Estudios Epistemológicos en Política Educativa, 2017)
This paper addresses the meaning of the expression. "epistemologies of education policies" clarifying concepts linked to it such as gnosiology, theory of knowledge, science and politics and practical sciences. Taking into consideration that practical sciences imply the dialectic relation between theory and practice, we got to the conclusion that the epistemological analysis of education practices implies the comprehension of the education policy as an activity carried out in the intersection between two practical sciences: the political science and the pedagogical science.